1997
DOI: 10.1021/jp971544z
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Derivatized Nanocrystalline Arrays of Gold, Silver, and Platinum

Abstract: A simple procedure has been developed to prepare thiol-derivatized nanoparticles of metals. The procedure involves the transfer of well-characterized metal hydrosols to a hydrocarbon medium containing the thiol. Thiol-derivatized nanoparticles Au, Ag, and Pt of near spherical shape forming nanocrystalline arrays have been characterized by X-ray diffraction, transmission electron microscopy (TEM), and other techniques. Thiolderivatized Au particles of mean diameters of 1.0, 2.1, and 4.2 nm from nanocrystalline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
211
2

Year Published

2000
2000
2004
2004

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 271 publications
(214 citation statements)
references
References 20 publications
1
211
2
Order By: Relevance
“…In metal colloids, surface plasmon excitations impart characteristic colors to the metal sols, the wine-red color of the gold sols being well-known. We found that colloidal particles of 4.2 and 2.1 nm diameters exhibit a distinct band around ~525 nm [9], the intensity of which increases with size. The intensity of this feature becomes rather small in the case of the 1-nm-diameter particles (£200 atoms).…”
Section: Electronic Structure Of Metal Nanoparticlesmentioning
confidence: 80%
See 1 more Smart Citation
“…In metal colloids, surface plasmon excitations impart characteristic colors to the metal sols, the wine-red color of the gold sols being well-known. We found that colloidal particles of 4.2 and 2.1 nm diameters exhibit a distinct band around ~525 nm [9], the intensity of which increases with size. The intensity of this feature becomes rather small in the case of the 1-nm-diameter particles (£200 atoms).…”
Section: Electronic Structure Of Metal Nanoparticlesmentioning
confidence: 80%
“…5. The metal particles form closepacked structures extending over tens of nms with a regular spacing of ~1 nm between them [9]. X-ray diffraction pattern of this array exhibits a low-angle peak corresponding to a d spacing of 5.0 nm (Fig.…”
Section: Two-dimensional Arraysmentioning
confidence: 99%
“…49,50 One of the most commonly studied classes of metallic nanoparticles consists of colloidal gold or silver crystallites that are nucleated and grown from metallic ions in solution and are stabilized by simultaneous attachments of alkanethiols HS-(CH 2 ) nϪ1 -CH 3 ͑or thiol derivatives͒ onto their surface ͑denoted as ''AuSCn'' or ''AgSCn''͒. 3,4,[29][30][31][32][33][34][35][36][37][52][53][54][55][56][57][58][59][60][61][62] Evidence that a 2D assembly of this class of nanoparticles may exhibit an interesting collective behavior under certain conditions has been provided by the recent studies of Langmuir films by Heath and co-workers. 3,4,34 -37,52,53 Their samples consisted of AuSCn (nϭ9, 12,18) and AgSCn (n ϭ3, 5,6,8,10,12) particles with mean metal-core diameters D ranging from 18 to 80 Å.…”
Section: Introductionmentioning
confidence: 99%
“…The clusters formed conducting arrays when linked by aryl dithiols or aryl di-isonitriles. Studies of Pt nanocluster arrays are limited to the work of Sarathy et al, [11] who were able to form arrays of limited coherent domain size with dodecanethiol capped Pt nanoclusters.…”
Section: Introductionmentioning
confidence: 99%